rSjP40 Inhibited the Activity of Collagen Type I Promoter via Ets-1 in HSCs - Jing Li (Frontiers Media S.A., 2021)
Liver fibrosis is a severe disease characterized by excessive deposition of extracellular matrix (ECM) components in the liver. Activated hepatic stellate cells (HSCs) are a major source of ECM and a key regulator of liver fibrosis. Collagen type I alpha I (COL1A1) is one of the main components of ECM and is a major component in fibrotic tissues. Previously, we demonstrated that soluble egg antigen from Schistosoma japonicum could inhibit the expression of COL1A1 in activated HSCs. In addition, studies have found that Ets proto-oncogene 1 (Ets-1) suppresses the production of ECM by down-regulating matrix related genes such as COL1A1 induced by transforming growth factor β, and ultimately inhibits liver fibrosis. In this study, the major aim was to investigate the effect and mechanism of Ets-1 on inhibiting COL1A1 gene promoter activity in HSCs by recombinant Schistosoma japonicum protein P40 (rSjP40). We observed the rSjP40 inhibited the expression of COL1A1 by inhibiting the activity of the COL1A1 promoter, and the core region of rSjP40 acting on COL1A1 promoter was located at -1,722/-1,592. In addition, we also demonstrated that rSjP40 could promote the expression of Ets-1, and Ets-1 has a negative regulation effect on the COL1A1 promoter in human LX-2 cells. These data suggest that rSjP40 might inhibit the activity of COL1A1 promoter and inhibit the activation of HSCs by increasing the expression of transcription factor Ets-1, which will provide a new experimental basis for the prevention and treatment of liver fibrosis.